The Implementation of Icloud System Based on Knowledge Sharing at The University of Maarif Hasyim Latih Sidoarjo - Achmad Fathoni Rodli (JETL (Journal of Education, Teaching and Learning), 2017)
This article presents the results of the analysis on the development of knowledge sharing processes and absorbs knowledge sharing activity, it is to increase the ability of the head of Departement at the University of Maarif Hasyim Latif and in innovating and in managing the Departement. The role of Information Technology in accommodating the knowledge sharing process is the development of the activities of managing and absorbing science courses to improve performance and provide added value and a competitive advantage in improving the quality performance of the head of Departement.  Design research is to find out how the problems that arise in the process of knowledge sharing and absorbing. Data collected by the identification of issues related to knowledge management based on Information Technology at the University of Maarif Hasyim Latif through observation, interviews, and documentation. Results of this study were to prove that iCloud system model developed at the University of Maarif has been contributing to 1) the implementation of the knowledge sharing process of the development activity of sharing and absorbing knowledge at the University Maarif Hasyim Latif to improve the innovation of ability. 2) Information technology has a major role in supporting the process of knowledge sharing on the development and absorbs knowledge sharing activities.